Intracranial abscess due to Prevotella bivia: First case report from India. (October 2020) - Samantaray, Subhashree; Biswas, Rakhi; Sasidharan, Gopalakrishnan Madhavan
Abstract: The association of Prevotella bivia ( P. bivia ), a Gram negative obligate anaerobic bacillus with brain abscess has been rarely reported. We hereby, report a case of brain abscess in a 50-year-old man, who suffered a head trauma followed by decompression surgery 10 months ago. Aspirated pus sample grew Methicillin resistant Staphylococcus aureus (MRSA) and P. bivia sensitive to metronidazole. The patient recovered well after a brain abscess evacuation surgery and post-operative metronidazole therapy, confirming the pathogenic role of P. bivia in this case. Highlights: Most brain abscesses are of polymicrobial etiology. This is the first report of brain abscess due to Prevotella bivia in India. P. bivia and other pathogenic anaerobic bacteria can be rapidly identified by the MALDI-TOF MS. Treatment with metronidazole for 10 days was found effective against this anaerobe.